2022
DOI: 10.3390/microplastics1010008
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence for Microplastic Contamination from Water-Soluble Detergent Capsules

Abstract: This study investigates the ability of water-soluble detergent capsules to effectively release microplastics from their composition. A total of 39 different brands of water-soluble capsulated detergents were tested, 20 of them for washing machines and 19 for dishwashers, from four different countries in the EU, i.e., Spain, Portugal, Belgium, and Italy, as well as two different devices for microplastic recovery from laundry wastewater. Wastewater samples from all laundry capsules reported microplastics, mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
3
1
1
Order By: Relevance
“…As can be seen in Figure S8 , 3.02 ± 0.33 MPs/g, 1.48 ± 0.39 MPs/g and 0.75 ± 0.34 MPs/g were found in detergents 1 (cube), 2 (cube) and 3 (pod), respectively. Bayo et al ( 2022 ) analysed 19 commercial brands of dishwashing detergents, finding lower values than those obtained in this study. The weight of each cube/pod was between 16 and 18 g, so detergent contributes between 12 and 52 MPs in each washing programme.…”
Section: Resultscontrasting
confidence: 84%
“…As can be seen in Figure S8 , 3.02 ± 0.33 MPs/g, 1.48 ± 0.39 MPs/g and 0.75 ± 0.34 MPs/g were found in detergents 1 (cube), 2 (cube) and 3 (pod), respectively. Bayo et al ( 2022 ) analysed 19 commercial brands of dishwashing detergents, finding lower values than those obtained in this study. The weight of each cube/pod was between 16 and 18 g, so detergent contributes between 12 and 52 MPs in each washing programme.…”
Section: Resultscontrasting
confidence: 84%
“…Additionally, many studies have provided estimates of microfiber emissions from synthetic textiles during machine washing. Numerous studies and results show that textiles are among the main potential polluters due to the release of fibres, and that one of the reasons for this is the washing process [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Research has shown that the type of construction itself affects the amount of microfibers released.…”
Section: Textiles—source Of Microplastic Pollutionmentioning
confidence: 99%
“…Its size, the type of material, the paint pigments it carries, the substances it absorbs, and the additives applied to plastic increase the harm of microplastics (Karbalaei et ). Some types have carcinogenic effects, as well as polylactic acid (PLA) produced due to the polymerization of lactic acid, which has recently been synthesized to bacteria through fermentation, and plastic types consumed by organisms in nature (Mehta et Bayo et al 2022). For this reason, microplastic detection is one of the phenomenal issues in recent times, and its detection is vital for humans and living life.…”
Section: Introductionmentioning
confidence: 99%